JDBC Metadata, MySQL, and Oracle Recipes A Problem-Solution Approach - Parsian, Mahmoud. (Apress : Imprint: Apress, 2006)
JDBC Metadata, MySQL, and Oracle Recipes is the only book that focuses on metadata or annotation-based code recipes for JDBC API for use with Oracle and MySQL. It continues where the authors other book, JDBC Recipes: A Problem-Solution Approach, leaves off. This edition is also a Java EE 5-compliant book, perfect for lightweight Java database development. And it provides cut-and-paste code templates that can be immediately customized and applied in each developer's application development.